5th Pay Commission Notification Regarding Central Civil Services (Revised Pay) Rules, 1997 (30th Sept 1997) - Planning Commission (Planning Commission, 1997)
The Fifth Central Pay Commission, constituted by the Government of India in 1994, submitted its report in January 1997 along with supplementary reports on employee motivation and Cabinet Secretariat. The Government, after careful consideration, broadly accepted the recommendations for civilian employees of Central Government Groups 'A', 'B', 'C', and 'D', as well as personnel in All India Services, with certain modifications. Key changes included revisions to six major pay scales (S-1 to S-5 and S-13), increasing fitment from 20% to 40% of pre-revised pay, and ensuring that employees receive at least one increment in the revised scale for every three increments in the old scale. The report also outlined procedures for arrears, implementation dates, and special provisions for specific categories such as Central Police personnel and certain departmental posts. Dearness Allowance calculations were to continue based on the All India Consumer Price Index for Industrial Workers with the base 1982, paid net of taxes, and applied from January 1, 1996. Non-Practising Allowance for doctors was standardized at 25% of basic pay with a ceiling. The resolution established uniform guidelines for pay fixation, compensation for price rise, and other allowances while ensuring transparency, equity, and compatibility with departmental structures, marking a comprehensive overhaul of the remuneration system for India’s central civil services.
Government of India, Planning Commission
Government of India, Planning Commission
Keywords: Fifth Pay Commission, Central Government Employees, Revised Pay Scales, Dearness Allowance, Fitment, Civil Services, All India Services, Non-Practising Allowance, Pay Fixation, Inflation Compensation, Annexure, Government Resolution